Utilizando tirinhas como ferramenta lúdica para o ensino de Física no ensino médio - Neves, Everaldo Martins (2017)
The development of this work is based on the learning theories of David Ausubel and Marco Antônio Moreira. The main proposal is the use of strips aimed at learning the concepts that permeate the discipline of physics, making the student observe and understand with greater clarity the physical phenomena that occur in their daily life; so that he, besides observing the phenomenon, can have a critical view on what is observed. The use of comic strips is a playful activity that can play an important role in the teaching of the contents of physics, because it causes the student to leave the abstraction and begin to think of the physics being used in the world closest to his reality. In addition, it is a way of "evading" the traditional method of teaching with chalk and chalk, making learning more meaningful, not simply using texts but also images. The strips used were collected from sites related to the study of physics (for example, Física e Vestibular, Dicas de Ciências, Centro Brasileiro de Pesquisas Física e Alicerces da Física) or produced by the professor himself. In order to verify the functionality of the method, a comparison was made between two classes, one with traditional classes and the other with the use of comics. We emphasize that there has been an improvement in the learning of the students we work with and a possibility to interconnect scientific knowledge and previous knowledge. At the end of the applications and analysis of the data obtained in the verifications, a script was produced to use the series to be used without physics teaching to be used in any secondary school.